Improving affinity of imprinted monolithic polymer prepared in deep eutectic solvent by metallic pivot - Wei, Ze-Hui; Sun, Xuan; Mu, Li-Na; Huang, Yan-Ping; Liu, Zhao-Sheng (Journal of Chromatography A, 2019)
•Metallic pivot strategy and deep eutectic solvent were well combined together.•The molecular modelling was undertaken to evaluate the stability of this system.•The affinity of the resultant imprinted monolith has been greatly improved.•Cetirizine can be efficiently extracted from ethanol solution by this monolith. One of the major drawbacks of conventional molecularly imprinted polymers (MIPs) is the requirements of volatility porogenic solvent during polymerization. To overcome the default, MIP based on deep eutectic solvent (DES, a new type of green designer solvents) has been synthesized successfully. To improve the affinity of the MIP based on DES, in this work, a strategy of metallic pivot was suggested in the first time to prepare a highly selective MIP monolithic column. A cetirizine-imprinted polymer was prepared in a DES-based porogen system composed of choline chloride/ ethylene glycol (ChCl-EG) in the presence of Co(Ac)2 as metallic pivot. The resulting DES- Co2+-MIP monolith had 23.5 times higher imprinting factor than the Co2+-free MIP monolith. The characterization of polymers indicated that DES was one of the primary factor influencing the MIP morphology and pore structure. Compared with previous metal-mediated and ionic liquid-based imprinted polymers, the introduction of DES as a porogen in polymerization led to higher imprinting factor (approximately 2.9 - 17.1 times). In addition, the resulting DES-Co2+-MIP can be used as an adsorbent for extraction of cetirizine from ethanol solution with the recoveries of 97.8%. As a conclusion, the metallic pivot is a rather valuable strategy for the synthesis of DES-based MIP monolith with high selectivity.